The Professional Rehabilitation of the INSS: analysis of the state capacities of the program in Tocantins (Gestão & Regionalidade, 2023)
Because of the recent changes in the social security policy, there is a panorama of uncertainty in the INSS Professional Rehabilitation policy, due to its weakening and institutional restructuring. In this sense, this research aims to analyze the state capacity of the Rehabilitation Program to achieve its institutional objectives. Institutional documents were consulted and interviews were carried out with professionals working at PRP - TO in Tocantins to identify technical-administrative and political-relational capacities. It was observed the existence of a highly qualified bureaucracy, however insufficient to meet the demand, limited capacity to guarantee financial resources to make basic operational issues feasible. Limitations were perceived in terms of internal and external coordination. At the political-relational level, there was a weakness in relations with other institutions, making it impossible to meet the diverse demands that permeate the transversal policies that dialogue with the PRP. Public sector investment is essential to overcome weaknesses in the capacities encountered.
Keywords: State Capacities; Social Security; Professional Rehabilitation